Factor VIII, von Willebrand Factor in Colorectal Cancer - Tuhta, A.; Yucel, I; Gonullu, G. (Oxford Univ Press, 2006)
…
Satellite Symposium on New Horizons for Gastric Cancer held in conjunction with the 8th World Congress on Gastrointestinal Cancer -- JUN 29, 2006 -- Barcelona, SPAIN